Hubungan Pengetahuan dan Stigma pada Keluarga dengan Beban Keluarga Dalam Merawat Pasien Skizofrenia di Wilayah Kerja Puskesmas Nanggalo Padang - Ziqni Ilma Al Wasi; Dewi Eka Putri; Renidayati Renidayati (Poltekkes Kemenkes Padang, 2021)
Families have a heavy burden in caring for ODS. Heavy load perceived by the family due to the level of family knowledge and family stigma. This study aims to determine the relationship knowledge and stigma on families with family burdens in caring schizophrenia patient in the working area of ​​Puskesmas Nanggalo Padang. Types of research this is correlation with the approach cross sectional. The population in this study is a family who cares for ODS in the working area of ​​Puskemas Nanggalo Padang and a sample of 87 people taken withPurposive Sampling. Data collection using a questionnaire Family Interview Scale / Stigma Items, questionnaire knowledge, and a questionnaire Zarit Burden Interview (ZBI). Research result It was found that more than half (59.8%) of the families experienced a heavy burden, more than half (57.5%) of families have a lower or higher level of knowledge half (52.9%) of families experienced high stigma. There is a relationship meaning between the stigma in the family and the family burden (p =0,000). There is no significant relationship between the level of family knowledge with family burden (p =0.110). It is expected that health workers, especially nurses soul in society to provide health education to the community regarding Schizophrenia. So that society no longer gives stigma to families who will make the family embarrassed in caring for ODS.